2017
DOI: 10.1002/ece3.3039
|View full text |Cite
|
Sign up to set email alerts
|

Postfire soil water repellency in piñon–juniper woodlands: Extent, severity, and thickness relative to ecological site characteristics and climate

Abstract: Wildfires can create or intensify water repellency in soil, limiting the soil's capacity to wet and retain water. The objective of this research was to quantify soil water repellency characteristics within burned piñon–juniper woodlands and relate this information to ecological site characteristics. We sampled soil water repellency across forty‐one 1,000 m2 study plots within three major wildfires that burned in piñon–juniper woodlands. Water repellency was found to be extensive—present at 37% of the total poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Furthermore, the litter did not consume any water. Therefore, an increase in the quantity of litter improved the soil's water permeability and retention capacity, and indirectly improved the soil's water-conservation function, as supported by the studies of Zvirzdin et al [19] and Wall and Heiskanen [20], respectively. Shallow groundwater is an important contributor to grassland moisture: the deeper the water table, the less compensation it provides for grassland moisture losses.…”
Section: Factors Influencing Grassland Water Storagementioning
confidence: 81%
“…Furthermore, the litter did not consume any water. Therefore, an increase in the quantity of litter improved the soil's water permeability and retention capacity, and indirectly improved the soil's water-conservation function, as supported by the studies of Zvirzdin et al [19] and Wall and Heiskanen [20], respectively. Shallow groundwater is an important contributor to grassland moisture: the deeper the water table, the less compensation it provides for grassland moisture losses.…”
Section: Factors Influencing Grassland Water Storagementioning
confidence: 81%
“…Despite this limitation in the study design, it can be assumed that areas with high cover of piñon and juniper trees may benefit most from reductions in soil−water repellency through anchor chaining because the canopy area is most susceptible to the development of soil−water repellency (Madsen et al, 2008(Madsen et al, , 2012a(Madsen et al, , 2012b(Madsen et al, , 2012cZvirzdin, 2012;Williams et al 2014). The need for effective postfire restoration treatments that address soil−water repellency issues will increase as piñon-juniper woodlands expand into historically dominant sagebrush/bunchgrass vegetation, increase cover in existing woodland communities, and promote large-scale wildfires.…”
Section: Discussionmentioning
confidence: 99%
“…Postfire anchor chaining may also improve seeding success by mitigating the effects of soil−water repellency as this condition is well documented in piñon-juniper woodlands (Jaramillo et al, 2000;Madsen et al, 2008;Madsen et al, 2012a;Roundy et al, 1978;Scholl, 1971;Zvirzdin, 2012). Although soil−water repellency is often present prior to fire, burning can increase its severity and spatial consistency (Doerr et al, 2000).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced infiltration capacity following fire has often been attributed to increased SWR (Dekker & Ritsema, ; Martin & Moody, ; Pierson et al, ). However, the substantial spatial variability in SWR at rangeland sites both before and after fire indicates that fire‐associated differences in infiltration are neither uniform nor persistent (Pierson et al, , ; Woods et al, ; Zvirzdin et al, ). Studies of postfire SWR in pine forests found SWR persisted from 1 to 6 years (Dyrness, ; MacDonald & Huffman, ).…”
Section: Introductionmentioning
confidence: 99%